First generation bioresorbable vascular scaffolds: do they hold the promise? - Elgendy, Islam Y.; Mahmoud, Ahmed N.; Anderson, R. David (Journal of Thoracic Disease, 2017)
The current generation of drug eluting stents (DES) exhibit a very low risk of stent thrombosis, restenosis, and need for repeat intervention (1). However, it took almost a decade for DES to reach this degree of maturation. Yet, these devices still carry a risk of very late stent restenosis and the need for repeat revascularization, due to the persistence of the metallic backbone and/or residual polymer once the anti-proliferative agent has completely eluted. As such, bioresorbable vascular scaffolds (BVS) hold the promise of offering an early anti-proliferative effect in addition to the mechanical support similar to DES for 2–3 years followed by complete bioabsorption. These effects are theoretically appealing. Complete bioabsorption could allow for preservation of the coronary vasomotion (which has been linked to the increased risks of late stent restenosis with DES), a possible reduction in the duration of dual antiplatelet therapy (DAPT) following the stent implantation, and the preservation of native coronary architecture which would allow for future surgical therapy.